TINGKAT KEPUASAN NASABAH TABUNGAN iB ATAS KUALITAS PELAYANAN PT. BANK PERMATA SYARIAH CABANG SEMARANG (Students' Journal of Economic and Management, 2014)
This study aimed to determine the extent to which the dimensions of service quality (Tangibles, Empathy, Assurance, Responsiveness, and Reliability) which has influence on Bank Permata Syariah Branch Semarang customer’s satisfaction. The type of study is a descriptive analytic. The data used in this study is the primary data obtained from questionnaires filled by the respondents. The population in this research is the entire customer tabungan  iB, the sample of 100 people who used the technique accidental-purposive sampling. Analysis of the data used in this study is the Importance and Performance Analysis and Cartesian Diagram  that will show the level of alignment between customer’s expectations and service performance. Keyword: customer satisfaction, service quality, Importance and Performance Analysis, Cartesian Diagram